HUBUNGAN ANTARA KONFORMITAS TEMAN SEBAYA DAN KONSEP DIRI DENGAN KEMANDIRIAN PADA REMAJA PANTI ASUHAN MUHAMMADIYAH KARANGANYAR - Susilowati, Krisna; Andayani, Tri Rejeki; Priyatama, Aditya Nanda (Jurnal Ilmiah Psikologi Candrajiwa, 2012)
ABSTRACT CORRELATION BETWEEN PEER CONFORMITY AND SELF CONCEPT WITH AUTONOMY OF ADOLESCENT IN PANTI ASUHAN MUHAMMADIYAH KARANGANYAR Krisna Susilowati Psychology Programme of Medical Faculty Sebelas Maret University Surakarta Autonomy is one of developmental tasks of the adolescent. It will rapidly develop in adolescence include the adolescent in orphanage. They required a high degree of autonomy as one way to entry into adulthood and that not having dependency on caregivers. Peer conformity and positive self concept will help adolescent in orphanage achieving autonomy. The purpose of this research isÂ  to determine: 1) positive correlation between peer conformity and self concept with autonomy of adolescent in orphanage; 2) positive correlation between peer conformity with autonomy of adolescent in orphanage; 3) positive correlation between self conceptÂ  with autonomy of adolescent in orphanage. The population of this research was adolescent in Panti Asuhan Muhammadiyah Karanganyar. They were 40 adolescent between 12 to 21 years old. This research was population research. The data were collected using Autonomy Scale, Peer Conformity Scale and Self Concept Scale. The validity of Autonomy Scale 0,249 â 0,571 and the realibility 0,851; The validity ofÂ  Peer Conformity Scale 0,257 â 0,548 and the realibility 0,823; and the validity of Self Concept Scale 0,254 â 0,653 with the realibility 0,887. Multiple Regression Analyse was conducted to analysed the first hypothesis and Partial Correlation Analyse to analysed the second and the third hyphothesis. The result of multiple regression analyse shows that correlation coefficient (R) 0,600; p = 0,000 ( p < 0,05) and F countÂ  10,399 > F Table 3,25 means that there is a positive correlation between peer conformity and self concept with autonomy of adolescent in Panti Asuhan Muhammadiyah Karanganyar. The partial result shows that the correlation ( r ) 0,442; p=0,0002 (p<0,05), it means that there is positive correlation between self concept and autonomy of adolescent in Panti Asuhan Muhammadiyah Karanganyar and there is no significant correlation between peer conformity and autonomy of adolescent in Panti Asuhan Muhammadiyah Karanganyar. It showed by correlation coefficient (r) 0,123; p=0,229 (p>0,05). Â  Keywords : Autonomy of adolescent in orphanage, Peer Conformity, Self Concept